Phonetic stability across time: Linguistic enclaves in Switzerland - Büchler, Andrin; Leemann, Adrian (Linguistik Online, 2022)
The present paper shows results of a proof-of-concept study on two historically related but geographically separated dialects of Swiss German. Between the 12th and 14th centuries, speakers of Valais German (southwestern Switzerland) emigrated to the southeastern part of the country, forming so-called Sprachinseln (enclaves) of Valais German in a Romansh-speaking area. Using an online survey, we collected responses from 300+ participants from the cantons of Valais and Grisons to examine how the two dialects have developed over time. Results suggest stability on the phonetic level, i. e. the two dialects still sound very similar despite having been geographically separated for 800 years. The morphosyntax and lexicon, however, exhibit substantial change. We discuss historic and sociodemographic factors that may explain these patterns.